Cloud Computing implementation level in Portuguese Companies - Ferreira, Osvaldo (2015)
The Information Technology (IT) has suffered many advances in recent years due to the development of new hardware and software solutions. These major changes have been noted in recent times in how we interact with applications and services in IT. Cloud Computing provides services and applications over the Internet with the promise of infinite capacity and service models of “pay-as-you-go”. This paper describes the main characteristics of Cloud Computing, future expectations and analyzes the state of knowledge and implementation in Portuguese companies.